Investigation of wt.% Si and Heat Treatment on the Mechanical Properties of Al6063 Aluminum Alloy by the Casting Product Propeller Shaft Model - EI Bhiftime (BIOMEJ, 2023)
Shaft propeller is one of the most important parts of ship propulsion installations. To produce a good quality shaft propeller, the ship propeller designer must consider various parameters, in order to produce the type and size of the propeller that has the value of effectiveness and high propulsion efficiency. Shaft propellers are usually made of steel but, in this study the propeller shaft model is made of Aluminum Alloy base material. So the material must have good mechanical properties. The purpose of this study is to see the mechanical properties of the sheller propeller with aluminum alloy base material with the addition of silicon elements and magnesium by going through the heat treatment process. The main base material used is 6063 aluminum alloy, with variations in the addition of Si (1, 2, 4 wt%). The addition of Mg can improve the mechanical properties of the casting. Alloy Al6063 is heated to a temperature of 790°C to reach a complete liquid state. Then the temperature is lowered to 645°C, then the Si element is inserted into the heating furnace and stirred. Then the temperature is lowered to 615°C, then the Mg element is added, then stirred thoroughly by a mechanical stirrer. The rotational speed of the stirrer is 70 rpm and the stirring time is 240 seconds. Then heated to a pouring temperature of 670°C. The mold is heated to a temperature of 265°C. Then poured into the mold and pressed 7 MPa. After that, it was allowed to stand for 600 seconds, and then removed from the mould. The cast propeller shaft is cooled at room temperature. Then the propeller shaft was heat treated with a solution treatment temperature of 485°C for 3600 seconds and then quenched using a fluid. After that, the casting products were treated with artificial aging. The results of the study are, Porosity will decrease along with the addition of Silicon elements. The lowest porosity level is in addition of 3% wt Silicon that is equal to 1.15%. Tensile test with the addition of 1% wt Silicon ie, 106.882 MPa, in addition of 2% wt Silicon that is, 128.713 MPa, and in addition of 3% wt Silicon ie 132.668 MPa. So the highest tensile stress value is at 3% wt. Hardness values will increase with the addition of Silicon elements. The highest hardness value found in the variation of 3% wt Silicon ie, 69.9 HB. While in the variation (0, 1, 2% wt) that is, 43.75 HB, 51.24 HB and 56.45 HB. So this study, proving that the addition of silicon elements can improve the mechanical properties of the shaft propeller.